Contract Law in the draft revision and update of the Civil Code (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2024)
The article analyzes the proposals of the contract subcommission for the reform of the Brazilian Civil Code, structured into four vectors: private autonomy and binding force; functional dimension (social and economic); legitimate trust and good faith; and modernization of general and specific rules. It explores the influence of the Economic Freedom Law, the codification of pre- and post-contractual good faith, and the inspiration from international models such as CISG and BGB for revision and resolution mechanisms.(Received: August 2024 | Accepted: October 2024)
Keywords: Contract Law; Private Autonomy; Civil Code Reform